Paz, Schoenberg, and Abel: an Examination of the Paths they Took Towards Atonality Based Statistical Features of Music. (Revista Argentina de Musicología, 2018)
The links between Juan Carlos Paz and Arnold Schoenberg are well-known, and strong. However, the way in which Paz left tonality behind has only partially been documented, and the relationships among his path towards atonality and that of Schoenberg, his reference point, are even less understood. The purpose of this work was to clarify these issues by focusing on voice-leading, particularly on the level of dispersal in the voice, and by comparing how the composers moved towards atonality through this parameter. In order to achieve this purpose, we analyzed the way in which intervals are distributed and organized in the vocal line of their songs. Results suggest that, within the framework of their songs, the Paz and Schoenberg approached atonality in a rather different fashion: Paz based melodic structure on lower levels of pitch dispersal (i.e., a larger amount of small intervals) and adhered to tonal rules of voiceleading more than Schoenberg did.
Keywords: Juan Carlos Paz; Arnold Schoenberg; tonality; atonality